EL ROL DEL ANTICICLÓN PACÍFICO EN LA CAÍDA DE NIEVE EN LOS ANDES ÁRIDOS - Arnobio G. Poblete; Mariela C. Hryciw (Boletín Geográfico)
This article aims to study in depth the role the anticyclone subtropical eastern South Pacific (ASPSO) on the nival precipitation in the arid Andes, its seasonal variability, fluctuations in the long and medium scale and associations with snowfall. For this reason, the incidence on the ratio of precipitation, the SST in the South Pacific Ocean, precipitable water, wind zonal, Radiation in Outgoing Long Wave and Omega were analyzed. The methodology consisted in the evaluation of the ASPSO through the definition of an index, based on Santiago de Chile (PSGO) measured surface atmospheric pressure. This would allow its surveillance and the processing of its temporal behavior in the statistical analysis. The results showed significant time - space associations within the involved variables, which confirmed in all cases the negative impact of ASPSO related to snowfall in the Andes mountains. period 1909-2015.